Assessment of Retail Practices for Providing Enhanced Value Added Services and Improved Customer Satisfaction Using Lean Manufacturing Approach - Shakoor, Mwafak; Qureshi, Mohamed Rafik; Abu Jadayil, Wisam; Jaber, Nasser (International Review of Management and Marketing, 2017)
The purpose of this study is to apply lean manufacturing principles in retailing services for enabling retail managers to understand takt time and value added services in order to achieve benchmarked retail efficiency. In-depth literature review on lean manufacturing research has been gauged and three potential retailers practising value added services have been identified for conducting the present case study. In situ, primary data have been captured and processed for necessary calculation. The notion of takt time has been introduced in retailing and a new concept of relative efficiency has also been developed to accomplish increased efficiency with more value added services (VAS). In order to provide more value added services, retail managers have to be lean thinking oriented. The results obtained in the three retailers are good enough to implement lean tools and enhance day to day efficiency at the outlets. Therefore; various improvement proposals have been identified along with managerial implications. Keywords: Lean Manufacturing, Lean principles, Relative efficiency, Retail stores, Takt time, Value added services (VAS). JEL Classifications: L81, M11